Overview of Adolescent Girls Knowledge about Personal Hygiene During Menstruation at Santa Monika Middle School, Pontianak: Elly Marce Titihalawa, Trysia Livy, Maria Goretik, Dwi Kurniasih, Pipin - Elly Marce Titihalawa; Trysia Livy; Maria Goretik; Dwi Kurniasih; Pipin (STIKes Persada Husada Indonesia, 2026)
Research Objective: Menstrual personal hygiene is an important component of adolescent reproductive health. Insufficient knowledge, limited school-based education, and inadequate disposal facilities may increase the risk of inappropriate hygiene behavior among adolescent girls. This study aimed to describe adolescent girls' knowledge and practices of personal hygiene during menstruation at Santa Monika Junior High School, Pontianak. Methodology: This study used a qualitative descriptive design. Ten grade VIII C female students who had experienced menstruation were selected through purposive sampling from 17 eligible students. Data were collected using structured in-depth interviews, observation of school hygiene facilities, field notes, and documentation. Interview data were analyzed thematically through familiarization, coding, categorization, theme development, and interpretation. Credibility was supported by participant confirmation, triangulation between interviews and observation, and supervisor review. Results: The analysis produced ten themes: understanding of menstruation, menstrual hygiene behavior, awareness of the importance of hygiene, genital cleaning practices, type of sanitary pad used, frequency of changing pads, management of used pads, frequency of changing underwear, cleaning of menstrual-stained underwear, and knowledge of the consequences of poor hygiene. Most participants showed basic knowledge of menstruation and reported appropriate hygiene practices, including changing pads two to five times per day and cleaning the genital area from front to back. However, several practices, particularly the management of used disposable pads and the routine use of feminine soap, require further health education. Conclusion: Adolescent girls generally demonstrated good knowledge and practices regarding menstrual personal hygiene, but school-based reproductive health education and supportive sanitation facilities remain necessary to sustain safe menstrual hygiene behavior.